Implementasi Algoritma Skipjack Untuk Mengamankan Audio - Harahap, Rahmadani (TIN: Terapan Informatika Nusantara, 2021)
One of the important things to ensure the confidentiality of data or information is encryption. Encryption uses an algorithm that can encode all bit streams of a message, skipjack is a 64-bit electronic codebook algorithm. The parameters used for encryption are 80-bit keys, and have 32 rounds for the encryption and decryption process. This algorithm can be used in one of the four modes specified in FIPS 81 for use in the Data Encryption Standard (DES). The algorithm that will be used for cryptography is said to be safe if it meets three criteria. The three criteria are the mathematical equations used must be complex, so that the algorithm is difficult to solve analytically, the cost used to solve the ciphertext exceeds the value of the information, and the time required to decipher the ciphertext exceeds the length of the information time. The strength of any encryption algorithm depends on its ability to withstand attacks. which is intended to determine the key or uncrypted communication. Broadly speaking, there are two types of attacks, namely brute-force and shortcuts. Therefore, in this paper we will discuss the extent to which the skipjack algorithm guarantees the security of hidden information.